MENIMBANG METODE JOHN WANSBROUGH DAN FAZLUR RAHMAN DALAM STUDI AL-QURAN - Machrus Machrus (Jurnal Theologia, 2013)
Abstract: One of aspects of Islam studied by orientalists is the Qur’an. They have written many books on the Qur’ān. One of themes of Qur’anic studies written by orientalists are about influences of Judeo-Christianity tradition in the Qur’ān. They try to prove the influences of Judeo-Christianity tradition in the Qur’ān. One of orientalists who try to prove the influences of Judeo-Christianity tradition in the Qur’ān is John Wansbrough, a Jewish orientalist. In studying the Qur’ān, Wansbrough uses literary analysis, an analysis based on the text apart from historical context. He does not believe in historical context relates to Qur’anic revelation. Whereas Qur’anic revelation relates to the events occurred in Muḥammad’s life time. By using historical approach, Fazlur Rahman proves that qur’anic revelation relates to the history so-called asbāb al-nuzūl. Rahman insists that the study of the Qur’ān done by Wansbrough does not make sense. Abstrak: Di antara aspek-aspek dalam Islam yang dikaji oleh para orientalis adalah al-Quran. Sudah banyak karya mengenai al-Quran yang dihasilkan oleh para orientalis. Sebagian dari karya orientalis mengenai al-Quran bertema¬kan pengaruh Yahudi-Kristen dalam al-Quran. Para orientalis mencoba untuk membuktikan adanya pengaruh Yahudi-Kristen. Salah satu dari mereka adalah John Wansbrough. Ia mengkaji al-Quran dengan menggunakan analisis sastera (literary analysis), suatu analisis yang didasarkan pada teks terlepas dari konteks sejarah. Ia tidak mempercayai bukti-bukti sejarah berkaitan dengan turunnya al-Quran. Padahal turunnya al-Quran berkaitan dengan peristiwa-peristiwa yang terjadi masa Nabi Muḥammad. Hal ini dibuktikan dengan analisis sejarah yang dilakukan oleh Fazlur Rahman. Rahman sendiri dengan tegas mengatakan bahwa kajian terhadap al-Quran yang dilakukan Wansbrough dengan menggunakan analisis sastera tidak masuk akal karena ada banyak kejanggalan. Kata-kata kunci: analisis sastera, Yahudi-Kristen, pengaruh, sejarah, Bibel.